The Role of Islamic Ethics in Shaping Public Policies for Sustainable Industrialization - Mariane, Ine; Kusnadi, Iwan Henri; Jamaludin, Maun (JURNAL AKTA, 2023)
The industrialization framework affects both the environment and society, yielding benefits such as reducing unemployment and improving welfare, but also causing environmental damage like water and air pollution. This research analyzes how public policies on environmental orientation in industrialization impact social-economic and ecological balance, environmental quality, and sustainable development in Bandung, Indonesia, from the perspective of Islamic principles. A quantitative methodology was employed, sampling 106 individuals, including entrepreneurs, civil servants, environmental specialists and public policy experts, and religious leaders from Bandung. A survey measured opinions on the balance of socio- economic and ecological factors related to industrialization with environmental quality and sustainability, all within the framework of Islamic teachings on stewardship (khalifah) and social justice (adl). Using Structural Equation Modeling (SEM), the findings revealed that industrialization significantly impacts social-economic balance, environmental balance, environmental quality, and sustainable development. These findings underscore the importance of balancing economic growth with environmental sustainability and advocate for policies grounded in religious values to achieve this balance.